2014
DOI: 10.1117/1.jmi.1.3.033506
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of contrast-enhanced spectral mammography depending on clinical indication

Abstract: Abstract. The objective is to optimize low-energy (LE) and high-energy (HE) exposure parameters of contrastenhanced spectral mammography (CESM) examinations in four different clinical applications for which different levels of average glandular dose (AGD) and ratios between LE and total doses are required. The optimization was performed on a Senographe DS with a SenoBright® upgrade. Simulations were performed to find the optima by maximizing the contrast-to-noise ratio (CNR) on the recombined CESM image using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 23 publications
(27 reference statements)
1
9
0
Order By: Relevance
“…Previous work from our group led to the development of the tungsten, molybdenum, and rhodium anode spectral models for mammography using interpolating polynomials (TASMIP M , MASMIP M , and RASMIP M , respectively; subscript “M” indicating application to mammography); these models used measured spectra from mammography x‐ray tubes of the past and addressed tube potentials from 20 to 42 kV. New applications in breast imaging utilize tube potentials up to 49 kV with exotic filtration — primarily for dual‐energy contrast‐enhanced imaging applications …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work from our group led to the development of the tungsten, molybdenum, and rhodium anode spectral models for mammography using interpolating polynomials (TASMIP M , MASMIP M , and RASMIP M , respectively; subscript “M” indicating application to mammography); these models used measured spectra from mammography x‐ray tubes of the past and addressed tube potentials from 20 to 42 kV. New applications in breast imaging utilize tube potentials up to 49 kV with exotic filtration — primarily for dual‐energy contrast‐enhanced imaging applications …”
Section: Introductionmentioning
confidence: 99%
“…New applications in breast imaging utilize tube potentials up to 49 kV with exotic filtration primarily for dual-energy contrast-enhanced imaging applications. [27][28][29][30] The two aforementioned mammographic spectral models do not address these higher tube potentials and modern target/filter combinations. In addition, no x-ray spectral model currently exists specifically for bCT.…”
Section: Introductionmentioning
confidence: 99%
“…Today, CESM is generally being used in a diagnostic setting. However, other potential clinical indications are being considered, including assessment of extent of disease, problem solving after non conclusive mammography and ultrasonography exams, screening of high-risk women, and CESM-guided biopsy 2,3 . To understand the clinical feasibility and find optimal imaging conditions, researchers continue to explore the parameter space of this modality 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Despite the promising results of CEM, there are concerns over radiation exposure and the potential for contrast reactions. Studies have shown CEM delivers an average glandular dose that is 20-80% higher than that of FFDM with a per-view average glandular dose range 0.43-2.65 mGy but below the United States Food and Drug Administration limit of 3 mGy specified by the Mammography Quality Standards Act regulations [30][31][32][33]. The adverse reaction rate to intravenous contrast agents is similar to that reported for CT; one meta-analysis found a 0.82% pooled rate of adverse reactions, of which 87% were mild reactions, and only one severe reaction occurred in 14,012 patients [33].…”
Section: Introductionmentioning
confidence: 99%